Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/elps.201200095
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative evaluation of Simon™, a new CE‐based automated Western blot system as applied to vaccine development

Abstract: Many CE-based technologies such as imaged capillary IEF, CE-SDS, CZE, and MEKC are well established for analyzing proteins, viruses, or other biomolecules such as polysaccharides. For example, imaged capillary isoelectric focusing (charge-based protein separation) and CE-SDS (size-based protein separation) are standard replacement methods in biopharmaceutical industries for tedious and labor intensive IEF and SDS-PAGE methods, respectively. Another important analytical tool for protein characterization is a We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…Once the proteins were separated within the pH gradient they were exposed to UV light and covalently cross-linked to a light-activated volume-accessible gel present in the microchip. This technique gave similar capture efficiencies (≈ 0.01%) to previous reports where proteins were immobilized on the inner surface of the capillary [42, 143]. Wash steps were performed by electrophoretic transport on the immobilized protein without concern of sample loss.…”
Section: Microchip Electrophoresissupporting
confidence: 55%
See 1 more Smart Citation
“…Once the proteins were separated within the pH gradient they were exposed to UV light and covalently cross-linked to a light-activated volume-accessible gel present in the microchip. This technique gave similar capture efficiencies (≈ 0.01%) to previous reports where proteins were immobilized on the inner surface of the capillary [42, 143]. Wash steps were performed by electrophoretic transport on the immobilized protein without concern of sample loss.…”
Section: Microchip Electrophoresissupporting
confidence: 55%
“…Simon™ also makes quantitative Western blots possible. Using this instrument, a standard curve was generated for a vaccine candidate protein with linearity from 0.45–7 µg/mL and R 2 values of 0.990 or greater for five experiments [42]. …”
Section: Techniquesmentioning
confidence: 99%
“…However, several of the concerns that plague non-automated western blotting will also affect automated western blotting. The use of capillary columns in some new automated machines [62,63] introduces new technical concerns including how we can relate some of the results from capillary electrophoresis westerns back to traditional western blotting results.…”
Section: Other Problems Associated With Inaccurate Quantification Of mentioning
confidence: 99%
“…Rustandi and colleagues applied size-CNIA to protein expression and identity in vaccine development. They reported that the technology increased the efficiency of analytical testing and could more effectively guide process development [63]. The group also developed a new improved method for detection of residual BSA to meet quality control requirements in vaccine production [64].…”
Section: Applicationsmentioning
confidence: 99%